Earthquake Mitigation in the Lisbon and Lower Tagus Valley area, Portugal - Carvalho, J. (2013)
The capital city of Lisbon and the Lower Tagus Valley region of central Portugal mainland are located in the Eurasian plate about 350 Km from the approximately E-W oriented Eurasia-Africa plate boundary. It is characterized by low slip-rates (<0.4 mm/year) and a moderate seismicity, occasionally shaken by some important historical earthquakes causing significant damages and economical losses. The most well know damaging earthquakes occurred in 1344, 1531, 1755, 1909 and 1969. The seismic hazard evaluation and mitigation of the area is therefore of great importance to this densely populated area. This paper focuses the evaluation of P- wave and S-wave seismic velocities of the shallowest surface using seismic refraction data interpretation and in- situ lithostratigraphic studies to obtain geotechnical parameters such as Vp/Vs ratios and the Poisson coefficient, estimated to provide information for future site effect studies and preliminary VS30 and soil classification maps. The information will also be used to correct earthquake records since this information was also collected close to the location of seismological stations. The soil classification is based upon the European Code 8 for civil engineering which was carried out for land use planning and design of critical facilities. Hundreds of available boreholes drilled for engineering (with SPT data) and water supply were used to confirm layer thicknesses and lithologies at depth together with a detailed geological survey of each profile area. It is the first time VS30 maps and a soil classification based on geophysical and geotechnical parameters is attempted for this highly populated region.